2011
DOI: 10.1002/jps.22426
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of m-cresol-induced Protein Aggregation Studied Using a Model Protein Cytochrome c

Abstract: Multi-dose protein formulations require an effective antimicrobial preservative (AP) to inhibit microbial growth during long-term storage of unused formulations. m-cresol is one such AP, but has been shown to cause protein aggregation. However, the fundamental physical mechanisms underlying such AP-induced protein aggregation are not understood. In this study, we used a model protein cytochrome c to identify the protein unfolding that triggers protein aggregation. m-cresol induced cytochrome c aggregation at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 57 publications
3
37
0
Order By: Relevance
“…APs may hydrogen bond with the peptide backbone, suggested by earlier studies on BA and polyproline monitoring changes in amide I, amide II, and hydroxyl bands using infrared spectroscopy (Strassmair et al 1969). The extent of aggregation seems to qualitatively correlate with the hydrophobicity of the AP (Singh et al 2011, Hutchings et al 2013). APs also have been suggested to interact with hydrophilic regions of proteins (Alford et al 2011).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…APs may hydrogen bond with the peptide backbone, suggested by earlier studies on BA and polyproline monitoring changes in amide I, amide II, and hydroxyl bands using infrared spectroscopy (Strassmair et al 1969). The extent of aggregation seems to qualitatively correlate with the hydrophobicity of the AP (Singh et al 2011, Hutchings et al 2013). APs also have been suggested to interact with hydrophilic regions of proteins (Alford et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been shown that these preservatives cause protein aggregation (Maa and Hsu 1996, Katakam and Banga 1997, Remmele Jr. et al 1998, Gupta and Kaisheva 2003, Tobler et al 2004, Roy et al 2006, Thirumangalathu et al 2006). We have demonstrated previously that APs used in liquid protein formulations lead to protein destabilization and aggregation using the model protein Cyt c (Singh et al 2010, Singh et al 2011, Hutchings et al 2013). The extent of this effect was dependent upon the nature of the AP, and the pattern of aggregation observed was CR > PH > BA > PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work we have focused our attention on cytochrome c, a protein recently used as a model to study protein aggregation (26). Model proteins offer several advantages as they are abundant and inexpensive, and their biophysics have been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Other parameter for Cyt C conformation investigation is an absorption band at 695 nm which measures the stability of a local protein region in Cyt C. This absorption band corresponds to the charge transfer from the side chain sulfur of the methionine residue (Met-80) to the heme ferric iron. Molecular loosening in Met-80 region leads to the absorption band absence due to lack of ligation of the amino acid to the heme [18]. Cyt C freezing leads to decreasing of absorbance band intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%